Polymer composites for thermal management: a review. Issue 9 (21st November 2016) - Vadivelu, M. A.; Kumar, C. Ramesh; Joshi, Girish M.
Abstract: The aim of this review article is to consolidate the important research works dedicated to polymers which are mainly used target material for heat transfer applications. The requirement of present day heat transfer equipment is compactness, lightweight, manufacturability, and lower cost. Materials like copper and aluminum though have better thermal conductivity but they are expensive and also heavy. Polymers are cheaper and easy to manufacture, recycle though they have sufficiently lower thermal conductivity compared to copper and aluminum. Polymer materials are thermally insulating material. It is too difficult to improve the amorphous nature of polymer material in order to achieve high thermal conductivity. One key path to increase the thermal conductivity of a polymer is to reinforce high thermal conductive fillers in the host matrix. In this review paper, an attempt is made to explore and summarize various key paths suggested by the researchers to develop high thermal conductive polymer composites.